Human action: treattise economics v.3 - Von Mises, Ludwig (Indiana: Liberty Fund, Inc., 2007)
Contiene: The imaginary construction of a socialist society. The impossibility of economic calculation under socialism. The governmentand the market. Interference by taxation. Interference with the structure of prices. Currency and credit manipulation